Traditional Chinese Exercise for Neurodegenerative Diseases: A Bibliometric and Visualized Analysis With Future Directions - Jiang, Buchan; Feng, Chengyao; Hu, Huiling; George, Daniel; Huang, Tianlong; Li, Zhihong (Frontiers in Aging Neuroscience, 2022)
Background: Traditional Chinese Exercise (TCE) has expanded out of China into the world and is frequently used in the prevention and treatment of many diseases. Although many studies have explored the ability of TCE as an intervention for neurodegenerative diseases, there are limited articles summarizing the research. The aim of this study was to investigate current research trends around TCE for neurodegenerative diseases and predict future directions for such research. Materials and Methods: Data was collected from the Web of Science Core Collection (WoSCC). All articles and reviews on TCE in relation to neurodegenerative diseases were retrieved. The data analysis was performed using CiteSpace (5.8R3) software, and the results were displayed in network maps. Results: The search identified 220 publications between 1999 and 2021. The USA was the most productive country (n=89), followed by China (n=68). The USA had the greatest centrality, indicating its tremendous global influence and close collaborations with other countries. Fuzhong Li from the Oregon Research Institute, USA, was not only the most prolific author (n=5), but also the most co-cited author (n=120). The Shanghai University of Sport contributed to the most publications (n=12). PLOS ONE was the most published journal, while Movement Disorders was the most cited journal. Tai Chi, Parkinson's disease, quality of life, balance, older adult were the most high-frequency keywords, while Alzheimer's disease had the highest centrality. Conclusions: The number of the publications on TCE related to neurodegenerative diseases has shown major growth in the past decade. However, there is a need for research institutions to strengthen cooperation between countries and institutions. Tai Chi, Parkinson's disease, Alzheimer’s disease, older adults and falls reduction have been the recent research focus. It is anticipated that in the future, Parkinson's disease will continue to be a central focus with the effects of Baduanjin, Wuqinxi, and Yijinjing requiring further research.